Activation of the proton sensing G-protein coupled receptor, GPR4, regulates focal adhesion dynamics and delays cell spreading due to increased cytoskeletal tension - Justus, Calvin Richard (East Carolina University, 2013)
The tumor microenvironment is characteristically acidic due to insufficient blood perfusion, chronic inflammation, hypoxia, and altered cell metabolism. The low pH found in the tumor microenvironment may facilitate the dissemination of cancer cells into the blood stream or lymph system by breaking down extracellular matrix components and degrading the basement membrane. In the murine B16F10 melanoma model, low pH has also been reported to activate the proton sensing G-protein coupled receptor, GPR4, and decrease cell migration in vitro as well as reduce pulmonary metastasis subsequent to tail vein injections. In this study we investigated delayed cell spreading found in B16F10 melanoma cells genetically modified to express GPR4 at a high level, namely B16/GPR4 cells. Attachment assays to tissue culture plates, fibronectin, glass coverslips, and matrigel established that B16/GPR4 cell spreading was significantly delayed when plated in media buffered to pH 6.4. Next, we investigated the specific heterotrimeric G-protein responsible for delayed B16/GPR4 cell spreading by using several chemical activators and inhibitors as well as numerous genetically engineered cell lines. Treatment with either C3-transferase (CT04), a direct Rho inhibitor, or a G12/13 inhibitory construct restored B16/GPR4 cell spreading significantly to a level similar to the vector control group and the physiological pH treatment group. We also evaluated the Gs and Gq G-protein pathways by using 2', 5'-dideoxyadenosine (DDA) and 8-bromo-cAMP or thapsigargin and a Gq inhibitory construct but found little modifications in B16/GPR4 cell spreading indicating the G12/13 G-protein pathway as the responsible variant. The downstream signaling mechanisms for delayed B16/GPR4 cell spreading were investigated. Both the ROCK inhibitor, Y27632, and the MLCK inhibitor staurosporine restored cell spreading. The same chemical inhibitors and activators as well as inhibitory constructs that restored B16/GPR4 cell spreading also reduced the formation of actin stress fibers indicating a proton-induced signaling cascade, which leads to increased cytoskeletal tension and delayed cell spreading. Due to the importance of focal adhesion dynamics in cell spreading and migration we next investigated two focal adhesion proteins that are vital for this process, phospho-paxillin (Y118) and phospho-focal adhesion kinase (Y397). The spatial localization of phospho-paxillin (Y118) and phospho-FAK (Y397) in B16/GPR4 cells after one-hour attachment assays is altered when treated with acidic media, displaying localization to the cell body instead of the cell periphery where dynamic focal adhesions are located. These results indicate that a proton-induced GPR4/G12/13/Rho/Rock/MLCK signaling pathway is responsible for delayed melanoma cell spreading and altered focal adhesion dynamics.
Keywords: Oncology; Biology, Cellular; Cellular biology; Rho-Associated Kinases; Melanoma; Receptors, G-Protein-Coupled; Models, Animal; Myosin-Light-Chain Kinase; Y 27632; TNF-Related Apoptosis-Inducing Ligand; GTP-Binding Proteins